2021
DOI: 10.5005/jp-journals-10071-23596
|View full text |Cite
|
Sign up to set email alerts
|

Opium-associated QT Interval Prolongation: A Cross-sectional Comparative Study

Abstract: A bstract Background Toxicity and side effects of long-term use of opioids are well studied, but little information exists regarding electrophysiological disturbances of opium consumption. While natural opium has been regarded safe to a great extent among traditional communities, concerns are emerging owing to the available evidence of QT prolongation that have been exposed during recent outcome surveillance of patients under opioid use. Potential QT prolonging interacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…A 61% prevalence was reported in Austria(21). Martell et al, reported a prevalence of 48.3% among 118 patients with opioid use disorder on methadone treatment (22), a prevalence of 54% in the United States of America(23), and 59.3% in India(24). The variations in the study population may explain the diversity in prevalence.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A 61% prevalence was reported in Austria(21). Martell et al, reported a prevalence of 48.3% among 118 patients with opioid use disorder on methadone treatment (22), a prevalence of 54% in the United States of America(23), and 59.3% in India(24). The variations in the study population may explain the diversity in prevalence.…”
Section: Discussionmentioning
confidence: 99%
“…The variations in the study population may explain the diversity in prevalence. In contrast, this study had younger; a study in India included opioid users who were older and with comorbid non-cardiac medical conditions(24).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…So, what is the reason for an increased mortality rate from COVID‐19 among individuals who use opium? According to a critical review of recent literature on short‐term effects of opium consumption, there are five main relevant reasons: (i) down‐regulation of anti‐viral cytokine expression such as interferon (IFN)‐α and IFN‐γ; (ii) development of pulmonary edema following endothelial dysfunction; (iii) increase thrombotic factors such as plasma fibrinogen and plasminogen activator inhibitor 1; (iv) increase ACE‐2 via stimulating silent information regulator 1 expression; (v) increased risk of pneumonia due to their effect on the medullary respiratory centers and decreased ventilation; and (vi) QT interval prolongation [ 7 , 8 , 9 ].…”
mentioning
confidence: 99%